Healthy bodies and young minds: late-nineteenth-century performer training in Australia. Issue 1 (2nd January 2016) - Arrighi, Gillian
Abstract : The focus of this article is the early incidence of organised training for young performers in Australia during the latter decades of the nineteenth century. Whilst there is ample evidence that traditional entry points to a professional stage career arose as the natural result of birth into a theatre-connected family, or childhood indenture to a theatre producer, this article reveals that several cases of institutionalised training were initiated by highly visible theatre identities from 1880 onwards. Adopting a modernising approach to the demands of a swiftly growing theatre industry, the popular actress/manager Rose Edouin Lewis and the theatre impresario J.C. Williamson each initiated performer training projects. In both cases, the target was young people of the middle class. Shining new light on archival materials from the turn of the twentieth century, this study reveals that the lineage of institutionalised performer training in Australia has a longer genealogy than theatre histories have previously allowed.